Peran TPA dalam Penyelenggaraan Pendidikan Al-Qur’an di Masjid Al-Fattah Palembang - Dedi Setiawan; Amir Rusdi; Vinny Aisyahlani Putri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Mentioning the Qur'an to children since childhood is easier than to teach the Qur'an as an adult.At this time, children have greater potential to learn and remember lessons. Quran Education Park (TPA) is a non-formal education institution that seeks to educate children from 7-12 years of age or elementary school age, so as to read, understand and practice the Qur'an. This research using qualitative descriptive approach. This research emphasizes on the role of education education of Al-Qur'an Quran Education Park (TPA). The population in this study as many as 6 teachers consisting of 1 male, 5 female and 31 students consisting of 17 men, 14 women. To obtain data author using observation data, interviews, test and documentation. Observation is to observe learning activity of Al-Qur'an Education Park (TPA), interview with santri guardian that is to know have been achieved the purpose of a educationin in Quran Education Park (TPA) and Tests to further prove from result of interview Done with students guardian. From the analysis, it can be concluded that from the 6 main objectives of the teaching of Al-Qur'an Education Park (TPA) can be said to play a good role in the education of Al-Qur'an as well as Wirutomo argued that David Berry's opinion was defined as a set of expectations To individuals who occupy certain social positions. From the opinion of David Berry it is clear that after doing the research of Al-Qur'an Mosque of Al-Qur'an (TPA) Al-Fattah Mosque has reached the desired expectations in accordance with the purpose of teaching the Education of Al-Qur'an (TPA).